One hand open palm technique for infant CPR - Patel, Shruti; Balikai, Shilpa; Elgin, Timothy G.; Newell, Elizabeth A.; Colaizy, Tarah T.; Raghavan, Madhavan L.; Atkins, Dianne L.; Haskell, Sarah E. (Frontiers in Disaster and Emergency Medicine, 2023)
Background The guideline recommended chest compression depth, rate, and recoil are essential factors for the return of spontaneous circulation (ROSC) in cardiopulmonary resuscitation (CPR). A pediatric resuscitation collaboration recently demonstrated that healthcare providers fail to meet the American Heart Association (AHA) guidelines, with the greatest difficulty being in achieving chest compression depth targets in infants. We hypothesized that the use of the heel of one hand [open palm technique (OPT)] will increase chest compression depth in infants compared to standard CPR techniques [two-finger technique (TFT), two thumb-encircling hand technique (TTT)]. Methods A prospective, randomized, single-center study was completed using an infant manikin. Thirty pediatric critical care providers performed 2 min of CPR for each technique followed by 5 min of rest. Each participant completed a survey at the end that assessed the difficulty level in order to assess the feasibility of this new technique. Results The mean chest compression depth for the OPT was significantly deeper compared to TFT (2.61± 0.63 cm vs. 2.25 ± 0.54 cm, p = 0.0004) but not significantly deeper compared to TTT (2.43 ± 0.46 cm, p = 0.0820). OPT was graded as the easiest technique, followed by TTT (2.20 ± 0.76 vs. 3.17 ± 0.95, p < 0.0001) and then TFT (3.38 ± 0.83, p < 0.0001). Conclusion The use of OPT for infant CPR resulted in improved chest compression depth. OPT was considered the easiest technique compared to standard infant CPR techniques, thus making it feasible to perform. Importantly, all providers failed to meet the AHA infant chest compression depth goal of 4 cm, regardless of the technique. Future research is needed to optimize CPR technique and performance to achieve targeted chest compression depth in infants.